Assessment of genetic variability and correlation among agro-morphological traits and spot blotch disease in a RIL population of wheat - Turan1, Rajita; Tyagi, Bhuedva Singh; Sharma1, Anil; Singh, Gyanendra; Singh, Virender; Ojha, Ashish (Journal of Cereal Research, 2017)
A study of genetic variability for various agro-morphological traits including spot blotch disease severity (DS) and grain yield (GY involving complete set of 214 recombinant inbred lines (RILs) population (cross â€˜Kanchan / Chirya 1) was conducted during 2014-15 and 2015-16 crop seasons. Combined analysis of variance (ANOVA) over years indicated that genotypes, environments and G Ã— E interactions were significant, indicating that the population exhibited significant differences for the traits studied. Similarly, variability analysis indicated wide genetic variation for all the traits among parents and recombinant inbred lines. Significant but negative correlation of disease severity (DS) with days to heading (DH), days to maturity (DM), plant height (PH) and grain yield (GY) indicated negative impact of high disease pressure on the expression of these traits. Among other agro-morphological traits, days to maturity showed significant positive correlation with plant height, grain yield and 1000-grain weight. High estimates of phenotypic and genotypic coefficient of variation (PCV and GCV) were found for disease severity (32.09 and 26.12 during 2014- 15 and 30.79 & 29.99 during 2015-16, respectively) followed by grain yield and 1000-grain weight. High estimates of heritability coupled with moderate to high values of genetic advance were recorded for most of the traits during both the years. The results indicated sufficient genetic variability, high estimates of heritability coupled with genetic advance along with desired correlation among traits, and therefore selection strategy might be effective in identifying promising genotypes possessing desired level of disease resistance, high yield and wider adaptability for target environments. Â Doi.org/ 10.25174/2249- 4065/2017/73499